Of Dogs and Dogmen: A History of Greyhound Racing in the United States: Review of Gwyneth Anne Thayer, Going to the Dogs: Greyhound Racing, Animal Activism, and American Popular Culture - Kendall-Morwick, Karalyn (Humanimalia, 2014)
Gwyneth Anne Thayer, Going to the Dogs: Greyhound Racing, Animal Activism, and American Popular Culture. Lawrence: UP of Kansas, 2013. 304 pp. 34.95 (hc).